MANFAAT UNIT PENGOLAHAN DAN PEMASARAN BAHAN OLAH KARET DALAM PENINGKATAN MUTU BAHAN OLAH KARET DAN PENDAPATAN USAHATANI KARET PADA PERKEBUNAN RAKYATDI KECAMATAN BANYUASIN III KABUPATEN BANYUASIN - Warih, Wijatmiko Sri Agung Dono; Batubara, Mustopa Marli; Sobri, Khaidir (Universitas Muhammadiyah Palembang, 2016)
This study aims to determine Benefits Processing Unit and Marketing Materials for Processing Rubber (UPPB) in improving the quality of the material for processing rubber on people rubber plantations in the District Banyuasin III, Banyuasin and How high the changes of rubber farmers' income before and after joining in Processing Unit and Marketing Materials for processing rubber in District Banyuasin III, Banyuasin.This research was conducted in the District Banyuasin III, Banyuasin. In April to June 2016. The research method used is survey method, for the withdrawal method example used Purposive Sampling and Simple Random Sampling. Data collection methods used in this study is observation and interviews directly to the respondents who have been determined by using the tools of questionnaires that had been prepared before. Data processing was performed using qualitative descriptive methods. The results showed that the change of unreal income between rubber farmers income before joining and after joining the agency assisted UPPB. And farmers membership in the UPPB group have no significant effect on the rubber farmers' income.